Influence of solidification rate on material properties of cast aluminium alloys based on Al–Si–Cu and Al–Si–Mg. (April 2015) - Okayasu, M.; Yoshida, S.
<x content-type="archive" xml:space="preserve">Abstract</x> Material properties of two different aluminium alloys (ADC12 and AC4C) were investigated using cast samples produced by conventional gravity and pressure casting at various solidification rates. The microstructural characteristics and defect density vary depending on the cast sample. Those material characteristics affect directly the mechanical properties. The mechanical properties, including tensile strength and fatigue strength, are improved with increasing solidification rate, due to the fine grains, very small eutectic structures and low dislocation density. Tensile strength and ductility for the AC4C alloy are overall higher than those for the ADC12 alloy. The reason for this is attributed to mainly the lower volume fraction of brittle Si- and Fe-based eutectic structures. The mechanical properties are more sensitive to the eutectic structures than to the grain size, although both factors affect the properties significantly. Dimple based ductile fracture is the main feature for the AC4C alloy, while cleavage based brittle failure is the dominant feature for the ADC12 alloy. Severe lattice strain occurs around the cracks in the AC4C alloy because of the high ductility, whereas weak lattice strain occurs in the brittle ADC12 alloy. On the basis of the microstructural and defect characteristics of the cast aluminium alloys, their tensile properties could be approximated using a proposed formula.